A Modified Three-Level Average Linear-Implicit Finite Difference Method for the Rosenau-Burgers Equation. (17th April 2014) - Janwised, Jiraporn; Wongsaijai, Ben; Mouktonglang, Thanasak; Poochinapan, Kanyuta
Abstract : We introduce a new technique, a three-level average linear-implicit finite difference method, for solving the Rosenau-Burgers equation. A second-order accuracy on both space and time numerical solution of the Rosenau-Burgers equation is obtained using a five-point stencil. We prove the existence and uniqueness of the numerical solution. Moreover, the convergence and stability of the numerical solution are also shown. The numerical results show that our method improves the accuracy of the solution significantly.